RESPON PETANI KARET THAILAND, INDONESIA, INDIA, DAN LAOS MENGHADAPI RENDAHNYA HARGA KARET - Iif Rahmat Fauzi; Lindawati Lindawati (Agro Estate, 2021)
Thailand is the largest natural rubber producer country in the world. In several years ago, the natural rubber price shows a negative trend. This condition make a rubber smallholder face difficulties in life. This paper aims to study efforts made by rubber smallholder to face low rubber prices. Methods in this paper used descriptive analysis with literature studies of the efforts undertaken by rubber smallholder in several rubber producer countries, especially in Thailand, Indonesia, India and Laos to face low rubber price. This study show that the alternative effort undertaken by rubber smallholder to face low rubber price generally was 1) management of cost production by reduced fertilizer and others factor production which no disturbed rubber income in short term condition; 2) develop other crops by intercropping technique on rubber side line; 3) looking for side jobs such as construction laborers, public transportation drivers, opening stalls and catching fish; 4) use of loans to maintain the standard of household living; 5) implement a joint marketing system to obtain a better rubber price; 6) selling or renting old and unproductive rubber land; and 7) renew/replanting rubber plantation.